Approximate Kelvin-Voigt Fluid Driven by an External Force Depending on Velocity with Distributed Delay - Yantao Guo; Shuilin Cheng; Yanbin Tang (Discrete Dynamics in Nature and Society)
We consider the approximate 3D Kelvin-Voigt fluid driven by an external force depending on velocity with distributed delay. We investigate the long time behavior of solutions to Navier-Stokes-Voigt equation with a distributed delay external force depending on the velocity of fluid on a bounded domain. By a prior estimate and a contractive function, we give a sufficient condition for the existence of pullback attractor of NSV equation.